The The Relationship between Nutrition Knowledge and Physical Activity with the Nutritional Status of Adolescents at SMP Negeri 2 Jogorogo, Ngawi Regency - Halqi, Najwa Laska; Andyarini, Esti Novi; Oktorina, Sarita (International Conference on Sustainable Health Promotion, 2025)
Adolescence is a transitional period characterized by accelerated physical growth and psychosocial changes, resulting in increased nutritional needs. Although the majority of adolescents have normal nutritional status, the prevalence of overnutrition is still quite high. One factor that can be related to nutritional status is nutritional knowledge and physical activity. This study aims to determine the relationship between nutritional knowledge and physical activity with nutritional status in ninth-grade adolescents at SMP Negeri 2 Jogorogo, Ngawi Regency. This study used a quantitative method with a correlational analytical approach and a cross-sectional design. The study population was all 30 ninth-grade students selected using a total sampling technique. The independent variables were nutritional knowledge and physical activity, while the dependent variable was nutritional status measured using the Body Mass Index for Age (BMI/U). Data were obtained through questionnaires and anthropometric measurements, then analyzed using the Chi-Square test and ordinal logistic regression with a significance level of 0.05. The results showed that the majority of respondents had good nutritional knowledge (80%), heavy physical activity (53.3%), and normal nutritional status (76.6%). However, the ordinal regression test results obtained a significance value of 0.612 (p > 0.05) and a McFadden's Pseudo R² of 0.026. This indicates that nutrition knowledge and physical activity are not significantly related to adolescent nutritional status, with an explanatory contribution of only 2.6%. Nutrition interventions for adolescents need to be implemented comprehensively, taking these various factors into account.